2014
DOI: 10.1007/s10900-014-9819-9
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Predictors of Non-compliance to Dietary Recommendations Among Hypertensive Patients

Abstract: Compliance to dietary recommendations among hypertensive people is a major health care issue. Non-compliance can nullify the effects of even the most scientific and optimum treatment plan. The main aim of this study was to determine the frequency and predictors of non-adherence in our region. We also investigated the possible factors based on patient opinions that could increase compliance. A sample of 400 adult patients, diagnosed with hypertension for at least 3 years, who visited Civil Hospital during the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 19 publications
5
21
2
1
Order By: Relevance
“…We found that approximately 30% individuals managed their diet, but the prevalence of diet management was not different between adults with and without hypertension, and dietary adherence score was much lower in those with hypertension than in those without. Such a low dietary adherence has been reported in previous studies; hypertensive patients showed the best adherence to medication, followed by lifestyle modifications such as drinking and physical activity, and was the poorest for diet [14,[20][21][22]. In particular, hypertensive patients taking BP-lowering drugs had much unhealthier lifestyles than those who were not taking medications [14,23].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…We found that approximately 30% individuals managed their diet, but the prevalence of diet management was not different between adults with and without hypertension, and dietary adherence score was much lower in those with hypertension than in those without. Such a low dietary adherence has been reported in previous studies; hypertensive patients showed the best adherence to medication, followed by lifestyle modifications such as drinking and physical activity, and was the poorest for diet [14,[20][21][22]. In particular, hypertensive patients taking BP-lowering drugs had much unhealthier lifestyles than those who were not taking medications [14,23].…”
Section: Discussionmentioning
confidence: 78%
“…In general, the consequence of not taking medication is relatively instant and distinct, whereas the impact of not modifying lifestyle appears to be less immediate and much smaller. For this reason, some people may have no expectation for nonpharmacological treatment [14] or may not feel the need for adopting a healthy lifestyle [20]. There also seems to be the incorrect belief that that a powerful drug can sufficiently address the harmful effects of unhealthy habits due to a lack of understanding regarding the mechanisms of BP regulation [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle advice given to promote lower salt intakes has had a positive effect on lowering salt consumption. Studies have reported the importance of a doctor or health worker's counseling on dietary salt control to lower blood pressure among hypertensive patients . Adherence to salt restriction is considered equally important as an antihypertensive drug .…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported history of CVDs patients. [34][35][36][37][38] Adherence to salt restriction is considered equally important as an antihypertensive drug. 39 The findings of salt-related knowledge of this study are similar to the findings of the 2016 STEPS survey in Samoa.…”
Section: Salt Consumption a Total N (%) P-value B Low N (%) High N (%)mentioning
confidence: 99%